Resistance in Lady Bird, a Movie by Greta Gerwig - Yuniar Fatmasari; Aniq Kanafillah (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
A movie is a work of literature bringing out perspective of social issue, to mention here is a woman in its relation with system of society. Resistance is one among several ways of how women interact with wider society. After watching Lady Bird movie written and directed by Greta Gerwig, the writers found that the idea of resistance is vividly seen. Thus, this study is to find out the main character’s resistance in the movie. To reveal the main character’s resistance, this study uses descriptive qualitative research so that all information, conditions, symptoms, and phenomena can be described in detail. There are two kinds of resistances found, the first is resistance toward the family and the second is resistance toward the wider society.